Preparation method of hole transport layer, solar cell and electric device thereof

NiOx films were prepared by magnetron sputtering, and hydrogen peroxide ultrasonic cleaning and SAMs modification technology were used to solve the problems of low conductivity and poor interface quality of the hole transport layer, achieving efficient hole transmission and improvement of solar cell performance.

CN119604160APending Publication Date: 2025-03-11CHANGZHOU S C EXACT EQUIP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411782025.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

When preparing the hole transport layer of solar cells in the prior art, holes cannot be effectively transmitted, and a large number of carriers are accumulated at the interface. The carrier transmission speed is low, and a non-radiative recombination process will occur, affecting the crystallinity of the upper perovskite layer film and limiting the photovoltaic performance of the device.

Method used

NiOx films were prepared by magnetron sputtering method, and the surface of NiOx film was modified by ultrasonic cleaning of hydrogen peroxide and self-assembly molecular material SAMs, which improved the conductivity and interface quality of the NiOx film and enhanced the hole transmission ability.

Benefits of technology

By improving the conductivity and interface quality of the NiOx film, the hole transmission efficiency is improved, the non-radiative recombination phenomenon is suppressed, and the crystallinity of the perovskite layer film and the photovoltaic performance of the solar cell are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604160A_ABST
    Figure CN119604160A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a hole transport layer, a solar cell and an electric device thereof. The preparation method of the hole transport layer of the solar cell comprises the following steps: 1, sputtering a layer of NiOx film on the surface of conductive glass by adopting a magnetron sputtering method; 2, putting the NiOx thin film substrate into a mixed solution of water and hydrogen peroxide for ultrasonic cleaning, and then cleaning with ethanol to obtain a modified NiOx thin film; 3, the modified NiOx film substrate is put into a mixed solution of SAMs and ethyl alcohol to be subjected to ultrasonic cleaning, then ethyl alcohol is used for cleaning, and a modified NiOx film is obtained; and 4, drying the modified NiOx thin film substrate, eliminating the residual solvent, heating and annealing to obtain the hole transport layer. The hole transport layer prepared by the invention is more matched with the energy level of the perovskite layer, and hole transport is facilitated; and non-radiative recombination at the interface can be inhibited, and the extraction of current carriers is facilitated. The performance of the perovskite solar cell is effectively improved, and processing of large-area devices is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cell preparation, and in particular to a method for preparing a hole transport layer of a solar cell, a solar cell and an electrical device thereof. Background Art

[0002] Due to the high efficiency, low cost, environmental friendliness and excellent photoelectric properties of perovskite materials, perovskite solar cells have developed rapidly and are expected to replace traditional silicon-based solar cells and become the dominant photovoltaic field. The common structure of perovskite solar cells can be divided into two types according to the incident direction of sunlight: formal (nip) and transverse (pin), where n refers to n-type semiconductor, i refers to perovskite layer, and p refers to p-type semiconductor.

[0003] Please refer to Figure 1 As shown in the figure, the basic structure of an inverse perovskite solar cell is generally composed of conductive glass (FTO), hole transport layer (HTL), perovskite layer, electron transport layer and electrode stacked in sequence. Inverse perovskite solar cells are widely used, can be used to prepare stacked cells, and have low-temperature processability and good stability. They are important device structures for commercialization. In existing inverse perovskite solar cells, NiOx (nickel oxide) thin films are mostly used as the hole transport layer of the device. Commonly used methods for preparing NiOx thin film hole transport layers include spin coating pre-prepared particles, sol-gel, magnetron sputtering, atomic layer deposition and pulsed laser deposition. Among them, the NiOx film prepared by magnetron sputtering has the advantages of good crystallinity, high flatness, uniform and stable surface. However, the NiOx film prepared by magnetron sputtering has the problem of low conductivity.

[0004] Since stoichiometric NiOx is originally an insulator, the conductivity of NiOx comes from the presence of many nickel vacancies in the NiOx film. However, due to the high ionization energy of nickel vacancies, the concentration of nickel vacancy defects is limited. Therefore, the conductivity of the untreated NiOx film (10 -4 cm -1 ) is low. The maximum valence band value of the NiOx film obtained by magnetron sputtering is usually not -5.4eV, which leads to the mismatch between the energy level of the untreated NiOx film and the perovskite layer, and the holes cannot be effectively transported, resulting in a large number of carriers accumulating at the interface.

[0005] In addition, there are a large number of defect sites between the untreated NiOx film and the perovskite layer interface, including oxygen vacancy defects, nickel vacancy defects in the NiOx film, and A-site vacancies, iodine vacancies, lead vacancies and other defects on the surface of the perovskite layer. These multi-type positively and negatively charged defect states will form localized electronic energy levels at the interface, and the energy levels of the defect states are different from the energy levels of carrier transmission. Therefore, the defect states will capture the transmitted charge and reduce the carrier transmission speed. On the other hand, non-radiative recombination processes may also occur.

[0006] From the above, we can see that the conductivity of the untreated NiOx film (10 -4 cm -1 ) is low; a large number of carriers are accumulated between the interface of the NiOx film hole transport layer and the perovskite layer; non-radiative recombination process may also occur.

[0007] At present, in the field of preparing NiOx (nickel oxide) thin film by magnetron sputtering, metal doping is used to solve the problem of low conductivity of NiOx thin film, or the interface passivation treatment of NiOx thin film by spin coating is carried out to accelerate the extraction of carriers. However, the interface passivation treatment by spin coating generally has poor uniformity and low coverage, which is not conducive to the extraction of carriers; the interface passivation layer of NiOx thin film will have multiple components and impurity residues, making the interface environment more complicated, and the rough surface also affects the crystallinity of the upper perovskite layer film, limiting the photovoltaic performance of the device. Since holes cannot be effectively transmitted, a large number of carriers are accumulated at the interface, and the transmission speed of carriers is low, non-radiative recombination processes will occur. These phenomena will lead to low device efficiency and accelerate device aging. In addition, the spin coating interface passivation layer is limited to the preparation of small devices, which is not conducive to the technical development of large-area devices. Summary of the invention

[0008] In order to solve the technical problems that holes cannot be effectively transmitted when preparing the hole transport layer of a solar cell in the prior art, a large number of carriers are accumulated at the interface; the carrier transmission speed is low, a non-radiative recombination process occurs, and the crystallinity of the upper perovskite layer film is affected, which limits the photovoltaic performance of the device, the present invention proposes a method for preparing a hole transport layer of a solar cell and a solar cell having the hole transport layer. The hole transport layer prepared by the present invention is more matched with the energy level of the perovskite layer, which is conducive to the transmission of holes. The surface of the NiOx film is modified by using self-assembled molecular materials SAMs, and the surface has good uniformity and high density. The non-radiative recombination at the interface can be suppressed, which is conducive to the extraction of carriers. It is also conducive to the technical development of large-area devices.

[0009] The method for preparing a hole transport layer of a solar cell provided by the present invention comprises the following steps:

[0010] Step 1, sputtering a layer of NiOx thin film on the surface of a conductive glass (FTO) substrate by a magnetron sputtering method;

[0011] Step 2, placing the NiOx thin film substrate in a first solution of water and hydrogen peroxide for ultrasonic cleaning, and then cleaning with ethanol to obtain a modified NiOx thin film;

[0012] Step 3, placing the modified NiOx thin film substrate in a second solution mixed with SAMs and ethanol for ultrasonic cleaning, and then cleaning with ethanol to obtain a modified NiOx thin film;

[0013] Step 4: drying the modified NiOx thin film substrate to eliminate residual solvent, and then heating and annealing to obtain the hole transport layer.

[0014] Preferably, the magnetron sputtering method is used to prepare NiOx thin film, with an oxygen flow rate of 5% and a vacuum degree of 1.3*10 -5 , pressure is 0.35Pa, speed is 6r / min.

[0015] Preferably, in step 2, the mixing ratio of water and hydrogen peroxide in the first liquid is 10:0.8-1.2, and the ultrasonic cleaning time is 10-12 minutes.

[0016] Preferably, in step 3, the mixing ratio of SAMs and ethanol in the second liquid medicine is SAMs / ethanol=5 mg / mL, and the ultrasonic cleaning time is 1 to 2 minutes, with the optimal time being 1 minute.

[0017] Preferably, the SAMs are one of 2Pacz [[2-(9H-carbazole-9-yl)ethyl]phosphonic acid], MeO-2Pacz [[2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid] or Me-4Pacz [[4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid].

[0018] Preferably, in step 4, the annealing temperature is 100-120° C. and the annealing time is 10-15 min.

[0019] The present invention also provides a solar cell, which comprises a hole transport layer prepared by the preparation method.

[0020] The invention also provides an electrical device, which comprises the solar cell.

[0021] The present invention is based on a NiOx film prepared by deposition, and the surface of NiOx is modified by ultrasonic cleaning with hydrogen peroxide, so that the valence band of the NiOx film is more matched with the energy level of the perovskite layer, which is beneficial to improve the hole extraction rate and improve its electrical performance. Then the NiOx substrate is placed in a mixed solution of SAMs and ethanol for ultrasonic passivation treatment. The surface of the NiOx film is modified by using self-assembled molecular materials SAMs, so that the surface uniformity is good and the density is high. The quality of the NiOx / perovskite interface is improved, the non-radiative recombination at the interface can be suppressed, and the extraction of carriers is beneficial. That is, after cleaning and modification, a SAMs layer is introduced on the surface of the NiOx film, so that it is more matched with the energy level of the perovskite layer, which is more beneficial to the extraction of holes.

[0022] Since the conductivity of conventional NiOx comes from the high-valent nickel ions present therein, and the high-valent nickel will induce the decomposition of perovskite and thus affect the life of the device. However, the second liquid solution mixed with SAMs and ethanol provided by the present invention is passivated on the NiOx film, so that SAMs exist between NiOx and the perovskite layer, and the direct contact between NiOx and the perovskite layer is cut off, so that the stability of the battery device is enhanced. This is because there are oxygen and nickel vacancy defects on the surface of the NiOx film, which together with the surface defects in the perovskite layer form multiple types of defect states, thereby forming localized electronic energy levels at the interface, limiting the movement of carriers, causing serious non-radiative recombination of carriers at the interface, and the chemical environment and defect state density between the interfaces will greatly affect the photoelectric properties of the film and the carrier transport process. Therefore, direct contact between the NiOx film and the perovskite layer will cause an increase in interface defects, and the introduction of SAMs between the NiOx film and the perovskite layer can passivate interface defects and improve device performance.

[0023] The advantage of using ultrasonic cleaning to passivate NiOx thin film is that the NiOx substrate can be placed in two different liquids, the first liquid and the second liquid, for treatment. During the ultrasonic cleaning process, NiOx will react chemically with the liquid, thereby achieving a passivation effect. That is, ultrasonic cleaning of the nickel oxide surface can both clean and passivate. By changing the solution used, large particles of dust can also be removed, the valence ratio can be optimized, and the process can be simplified and the cost can be reduced. Moreover, it can be prepared on a large scale and in large quantities, which is conducive to large-area device research. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the basic structure of an inverted perovskite solar cell;

[0025] Figure 2 The SEM image of the surface morphology of the perovskite film based on the comparative sample;

[0026] Figure 3This is a SEM image of the surface morphology of the perovskite film after NiOx cleaning based on the sample of Example 1;

[0027] Figure 4 The photocurrent density-voltage (JV) curves of the sample batteries of the comparative example and embodiment 1 are shown. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with the embodiments and drawings.

[0029] The method for preparing a hole transport layer of a solar cell provided by the present invention comprises the following steps:

[0030] Step 1: Place the FTO substrate in a magnetron sputtering device, and sputter a NiOx film on the FTO substrate.

[0031] Among them, the oxygen flow rate is 5% and the vacuum degree is 1.3*10 -5 , pressure is 0.35Pa, speed is 6r / min.

[0032] Step 2: Place the substrate with the NiOx thin film in a first solution of water and hydrogen peroxide for ultrasonic cleaning, and then clean it with ethanol to obtain a substrate with a modified NiOx thin film. The first solution has a mixing ratio of water and hydrogen peroxide of 10:0.8-1.2, and the ultrasonic cleaning time is 10-12 minutes.

[0033] Ultrasonic cleaning uses the high-frequency oscillating electrical signal generated by its generator, which is converted into high-frequency mechanical vibration through a transducer and propagated into the liquid medicine to clean and passivate the NiOx film. Its working mechanism is to use cavitation to increase the cleaning and passivation effect by multiples or dozens of times. When a beaker containing liquid medicine is placed in a cleaning machine and ultrasonic waves are applied, ultrasonic waves are a high-frequency wave that is sparse and dense and radiates in the liquid medicine, which will cause the liquid medicine to vibrate back and forth at high speed. In the negative pressure area of ​​the vibration, countless tiny vacuum bubbles will be formed because the surrounding liquid cannot be replenished in time, while in the positive pressure area, the tiny bubbles suddenly close under pressure. During the closing process, the liquids collide with each other to form an instantaneous high pressure, which acts on the NiOx film being cleaned and passivated.

[0034] In NiOx films prepared by magnetron sputtering, nickel compounds mainly exist in Ni 2+(Ni(OH)2 or NiO), which leads to low conductivity and shallow Fermi level and valence band maximum (VBM) level, thus preventing sufficient hole transfer from the photoactive material to the NiOx hole transport layer. Ultrasonic passivation of NiOx film with hydrogen peroxide can make the NiOx valence band more matched with the perovskite layer energy level, which is beneficial to improve the hole extraction rate and improve its electrical properties. 3+ The ratio of NiOx to Ni(OH)2 increases and forms NiOOH (from Ni(OH)2), a stable component with high conductivity. The presence of NiOOH also introduces more surface hydroxyl groups for SAMs binding. In addition, this treatment prevents the aggregation of NiOx nanoparticles.

[0035] Step 3, placing the substrate with the modified NiOx thin film in a second solution of SAMs and ethanol for ultrasonic cleaning, and then cleaning with ethanol to obtain a substrate with the modified NiOx thin film. The SAMs and ethanol mixture ratio of the second solution is SAMs / ethanol = 5 mg / mL, and the ultrasonic cleaning time is 1 to 2 minutes, and the optimal time is 1 minute.

[0036] The SAMs can be one of 2Pacz [[2-(9H-carbazole-9-yl)ethyl]phosphonic acid], MeO-2Pacz [[2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid] or Me-4Pacz [[4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid].

[0037] The second liquid is used for ultrasonic treatment, so that the SAMs are combined with the NiOx film, that is, the surface of the NiOx film is modified. Because SAMs itself has the function of transferring holes, the phosphate groups on its molecules can suppress the defects on the surface of the NiOx film and passivate the surface of nickel oxide. When SAMs are deposited on the NiOx film, the number of surface hydroxyl groups will increase, which will promote the formation of P=O / Ni. SAMs covering the NiOx film layer can promote the proper nucleation and growth of the perovskite layer on the hole transport layer. In addition, the more hydrophobic NiOx / SAMs can induce an excellent perovskite layer with larger grains and high crystallinity.

[0038] Step 4: Place the substrate with the modified NiOx film in an oven for drying to eliminate the residual solvent, and then place it on a hot plate for heating and annealing to obtain a substrate with a hole transport layer. The annealing temperature is 100-120° C. and the annealing time is 10-15 minutes.

[0039] The hole transport layer is composed of NiOx, which is cleaned and passivated with hydrogen peroxide and SAMs ultrasonic waves to improve the overall quality and performance of the NiOx film.

[0040] The following is an example of preparing an inverse perovskite solar cell according to the method for preparing a hole transport layer proposed in the present invention.

[0041] Embodiment 1:

[0042] Step 1: Place the FTO substrate in a magnetron sputtering device, and sputter a NiOx film on the FTO substrate.

[0043] Among them, the oxygen flow rate is 5% and the vacuum degree is 1.3*10 -5 , pressure is 0.35Pa, speed is 6r / min.

[0044] Step 2: Place the substrate with the NiOx thin film in a first solution of water and hydrogen peroxide for ultrasonic cleaning, and then clean it with ethanol to obtain a substrate with a modified NiOx thin film. The first solution has a mixing ratio of water and hydrogen peroxide of 10:0.8, and the ultrasonic cleaning time is 10 minutes.

[0045] Step 3: Place the substrate with the modified NiOx thin film in a second solution of SAMs and ethanol for ultrasonic cleaning, and then clean it with ethanol to obtain a substrate with the modified NiOx thin film. The second solution of SAMs and ethanol has a mixing ratio of SAMs / ethanol = 5 mg / mL, and the ultrasonic cleaning time is 1 min.

[0046] The SAMs can be one of 2Pacz [[2-(9H-carbazole-9-yl)ethyl]phosphonic acid], MeO-2Pacz [[2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid] or Me-4Pacz [[4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid].

[0047] Step 4: Place the substrate with the modified NiOx film in an oven for drying to eliminate the residual solvent, and then place it on a hot plate for heating and annealing to obtain a substrate with a hole transport layer. The annealing temperature is 100° C. and the annealing time is 10 minutes.

[0048] The above-mentioned ultrasonic cleaning and passivation treatment of the NiOx film using hydrogen peroxide solution and SAMs and ethanol mixed solution improves the overall quality and performance of the NiOx film, and finally, after heating and annealing, the hole transport layer provided by the present invention is obtained. Then, a perovskite layer, an electron transport layer and an electrode are sequentially prepared on the hole transport layer to obtain a trans-perovskite solar cell (please refer to the Figure 1 ).

[0049] The basic preparation scheme of Example 2-Example 5 is the same as that of Example 1, except that the preparation process parameters are as follows:

[0050] Embodiment 2:

[0051] The first liquid contained water and hydrogen peroxide in a mixing ratio of 10:1.0, and the ultrasonic time was 10 min; the second liquid contained a concentration of 5 mg / mL (SAMs:ethanol), and the ultrasonic time was 1 min.

[0052] Embodiment 3:

[0053] The first liquid had a water-to-hydrogen peroxide mixture ratio of 10:0.8, and the ultrasonic time was 12 min. The second liquid had a concentration of 5 mg / mL (SAMs: ethanol), and the ultrasonic time was 1 min.

[0054] Embodiment 4:

[0055] The first liquid contained water and hydrogen peroxide in a mixing ratio of 10:0.8, and the ultrasonic time was 10 min. The second liquid contained a concentration of 5 mg / mL (SAMs: ethanol), and the ultrasonic time was 1 min.

[0056] Embodiment 5:

[0057] The first liquid contained water and hydrogen peroxide in a mixing ratio of 10:0.8, and the ultrasonic time was 10 min. The second liquid contained a concentration of 5 mg / mL (SAMs: ethanol), and the ultrasonic time was 2 min.

[0058] Based on the hole transport layer prepared by the present invention, five samples of the embodiment of the inverted perovskite solar cell were prepared. Then, the interface of the NiOx film was passivated by the spin coating method in the prior art to prepare the sample of the comparative example of the inverted perovskite solar cell.

[0059] like Figure 1 The figure shows the schematic diagram of the structure of an inverted perovskite solar cell.

[0060] Electrode—Ag; electron transport layer—for example, C60 (carbon 60); hole blocking layer—BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline); perovskite layer—perovskite; hole transport layer—NiOx, self-assembled molecular material SAMs; membrane—FTO (transparent conductive film); glass—glass.

[0061] The battery performance of five example samples and one comparative example sample prepared in the present invention is tested below.

[0062] According to international standards, the photovoltaic parameters - open circuit voltage (Voc), short circuit current density (Jsc), and fill factor (FF) - can be obtained by using a solar simulator (AM 1.5G) to test the photoelectric conversion efficiency (PCE) of the device. The test data values ​​are shown in Table 1.

[0063] Scanning electron microscopy (SEM) was used to detect the surface morphology, grain size and distribution of the perovskite film.

[0064] Test steps: Place the battery in the fixture, link it to the source meter, and obtain the corresponding device parameters through the test software.

[0065] Table 1

[0066]

[0067] By comparison, it was found that the nickel oxide substrate was placed in the first solution with different concentrations and the second solution for ultrasonic cleaning and passivation for different times. The solution concentration and ultrasonic time would directly affect the quality of the nickel oxide film. On this basis, a complete perovskite device was prepared for performance testing. According to the experimental results, the battery device prepared in Example 1 can obtain the best performance.

[0068] like Figure 2 As shown in FIG. 1 , it is a scanning electron microscope (SEM) image of the surface morphology of the perovskite film without using the method of the present invention to clean the nickel oxide. Figure 3 As shown, it is an SEM image of the surface morphology of the perovskite film after the nickel oxide is cleaned by the method of the present invention based on Example 1. The perovskite film deposited on the nickel oxide substrate that has not been cleaned is of poor quality, the grain size of the perovskite film is small, the grain shape is irregular, the size difference is large, and the grain boundary gullies are obvious. Relatively speaking, the perovskite film deposited on the nickel oxide substrate after cleaning by the present invention is more dense and uniform, and the average size of the grains is effectively increased to obtain a high-quality perovskite film. The larger grain size means the reduction of the grain boundaries on the surface of the film, which can effectively block the interference of external air and moisture, and the stability of the perovskite film is enhanced, which is beneficial to the stability of the device. Analyzing and comparing the efficiency of the battery, the cleaning and passivation effect of Example 1 is the best. If the concentration of the first liquid and the time of the ultrasonic wave are increased, it will lead to the transition of the cleaning of the NiOx film. The ultrasonic wave time of the second liquid is too long, which is easy to damage the surface of NiOx, resulting in an increase in defects.

[0069] like Figure 4 As shown in the figure, the photocurrent density-voltage (JV) curve of the inverse perovskite solar cell obtained under standard AM1.5G illumination. The black curve below is based on the cell curve without cleaning and passivation; the red curve above is based on the cell curve after cleaning and passivation of the nickel oxide film in Example 1. Figure 4 It can be seen that the photoelectric conversion efficiency (PCE) of the device after cleaning in Example 1 is 22.10%, V OC is 1.12V, J SC 24.34 mA / cm 2 , FF is 81.08%. In contrast, the performance of the device without cleaning and passivation is poor, with a PCE of 18.04% and a V OC is 1.07V, V OC 23.27mA / cm 2 , FF is 72.45%.

[0070] It can be concluded that the cleaning and passivation method of the present invention can effectively improve the performance of perovskite solar cells. The improvement of the photovoltaic performance of the cell is due to the improvement of the quality of the perovskite film. The increase in perovskite grains reduces the grain boundaries, and the increase in crystallinity reduces the defect state density of the perovskite film and reduces the voltage loss. At the same time, the uniform large perovskite grains enhance the light absorption capacity, inhibit the charge recombination, and obtain a higher short-circuit current and fill factor.

[0071] The above description is only a specific implementation of the present invention. It should be pointed out that any modification, equivalent substitution and change made within the spirit and framework of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a hole transport layer of a solar cell, comprising the following steps: Step 1, sputtering a NiOx film on the surface of a conductive glass substrate; Step 2, placing the substrate with the NiOx thin film in a first solution mixed with water and hydrogen peroxide for ultrasonic cleaning, and then cleaning with ethanol to obtain a substrate with a modified NiOx thin film; Step 3, placing the substrate with the modified NiOx thin film in a second solution mixed with SAMs and ethanol for ultrasonic cleaning, and then cleaning with ethanol to obtain a substrate with the modified NiOx thin film; Step 4: drying the substrate with the modified NiOx thin film to eliminate the residual solvent, and then heating and annealing to obtain the hole transport layer.

2. The preparation method according to claim 1, characterized in that The magnetron sputtering method is used to prepare NiOx thin film, with an oxygen flow rate of 5% and a vacuum degree of 1.3*10 -5 , pressure is 0.35Pa, speed is 6r / min.

3. The preparation method according to claim 1, characterized in that: In the step 2, the mixing ratio of water and hydrogen peroxide in the first liquid is 10:0.8-1.2, and the ultrasonic cleaning time is 10-12 minutes.

4. The preparation method according to claim 1, characterized in that: In step 3, the mixing ratio of SAMs and ethanol in the second liquid medicine is SAMs / ethanol=5 mg / mL, and the ultrasonic cleaning time is 1 to 2 minutes.

5. The preparation method according to claim 1, characterized in that: The SAMs are one of 2Pacz [[2-(9H-carbazole-9-yl)ethyl]phosphonic acid], MeO-2Pacz [[2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid] or Me-4Pacz [[4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid].

6. The preparation method according to claim 1, characterized in that: In step 4, the annealing temperature is 100-120° C. and the annealing time is 10-15 min.

7. A solar cell, characterized in that: The invention comprises a hole transport layer prepared by the preparation method according to any one of claims 1 to 6.

8. An electrical device, characterized in that: Comprising the solar cell according to claim 7.

Citation Information

Cited By

  • NiOx-HTL cleaning method based on oxygen-alkali micron bubble system

    CN121017163A